Comparative Study: Social Competence of Children in the United Arab Emirates and Iraq - Al-Taii, Alaa Abdullah (Al-Adab Journal, 2019)
Physical, psychological, and socio-cultural traits may vary, globalization has increased the range of differentiation through mass movements, developments in communication technology, and the recent penetration of the values of subcultures in dominant cultures, leading to the concept of multi-cultural societies. Comparative studies are becoming increasingly significant in sociological research, as in this study which investigates the differences in children’s social competence within contemporary communities. To understand social competence, researchers must consider its social context. Analysis of the national context of children’s behavior must be developed to understand the culture of the children of a country, particularly, in a world where the phenomena of globalization and convergence are a reality. The present study aims to identify the differences in the levels of social competence of children from Iraq and the United Arab Emirates by administering a social competence questionnaire to 300 children. The results reveal a significant difference.